PERAN MEDIA SOSIAL INSTAGRAM DALAM PEMBENTUKAN IDENTITAS REMAJA - Sindy Ramadhani (Triwikrama: Jurnal Ilmu Sosial, 2024)
The formation of adolescent identity is a complex process influenced by psychological and social aspects that evolve with life experiences. In the digital era, social media platforms like Instagram play a significant role in this process, providing a space for teenagers to express themselves and shape their self-identity based on social perceptions. This study aims to explore the role of social media, specifically Instagram, in the identity formation of adolescents. Using a qualitative method, this research involved adolescents aged 18-24 years as subjects. Data collection techniques utilized a questionnaire designed to deeply understand the perceptions and experiences of teenagers in using Instagram as a medium for identity formation. The results indicate that Instagram significantly impacts the way adolescents build and present their identities, both positively as a space for self-expression and as a challenge due to social pressures encountered through online interactions. These findings provide valuable insights into the dynamics of adolescent identity in the digital era and how social media affects their self-perception.